2019
DOI: 10.1039/c9tc00795d
|View full text |Cite
|
Sign up to set email alerts
|

Dysprosium-activated scheelite-type oxides as thermosensitive phosphors

Abstract: A systematic investigation of the thermometric response of dysprosium-activated scheelite-type oxides demonstrates their potential as optical sensors for intermediate temperatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…When discussing our results, we refer to the luminescence spectra presented in Figures 6-10 and the energy level scheme in Figure 11 that was constructed based on the low temperature absorption spectra shown in References [31][32][33][34][35]. [28] -0.41 GdVO 4 [22] 1.80 -Na 5 La 0.5 Dy 0.5 (WO 4 ) 4 [30] 1.80 0.30 NaDy(MoO 4 ) 2 [30] 0.75 0.38 YNbO 4 [24] 1.40 0.36 Y 3 Al 5 O 12 [28] -0.44 La 3 Ga 5.5 Ta 0.5 O 14 [25] 1.47 0.34 BaYF 5 [26] 1.10 0.25 Gd 2 Ti 2 O 7 [27] 1.20 -K 3 Y(PO 4 ) 2 [45] 1.31 -Ba 3 Y 4 O 9 [46] 1.34 - [30].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When discussing our results, we refer to the luminescence spectra presented in Figures 6-10 and the energy level scheme in Figure 11 that was constructed based on the low temperature absorption spectra shown in References [31][32][33][34][35]. [28] -0.41 GdVO 4 [22] 1.80 -Na 5 La 0.5 Dy 0.5 (WO 4 ) 4 [30] 1.80 0.30 NaDy(MoO 4 ) 2 [30] 0.75 0.38 YNbO 4 [24] 1.40 0.36 Y 3 Al 5 O 12 [28] -0.44 La 3 Ga 5.5 Ta 0.5 O 14 [25] 1.47 0.34 BaYF 5 [26] 1.10 0.25 Gd 2 Ti 2 O 7 [27] 1.20 -K 3 Y(PO 4 ) 2 [45] 1.31 -Ba 3 Y 4 O 9 [46] 1.34 - [30].…”
Section: Resultsmentioning
confidence: 99%
“…In another paper, E. Hertle et al [29] reported the in-depth investigation of (Gd,Lu)AlO 3 :Dy 3+ and (Gd,Lu)Al 5 O 12 :Dy 3+ , unraveling the effect of substituting Gd 3+ by Lu 3+ ions on the garnet structure durability and the spectroscopic features of these luminescent materials. Perera and Rabufetti [30] reported the investigation of the thermosensitive properties of polycrystalline NaLa 1-x Dy x (MO 4 ) 2 and Na 5 La 1-x Dy x (MO 4 ) 4 (M = Mo, W) materials, with special attention paid to the structural implication and the effect of Dy 3+ concentration. All Dy 3+ -doped systems mentioned above were prepared in a polycrystalline form by a high temperature solid state reaction.…”
Section: Introductionmentioning
confidence: 99%
“…We observe that, upon X-ray excitation of core La 3+ electrons, the generated electron−hole pairs are thermalized, thereby populating not only the 4 F 9/2 state but also the 4 I 15/2 state of Dy 3+ ; luminescence emission from these states yields bands at 570 and 540 nm, respectively. 14,20 The observed emission from thermally populated state 4 I 15/2 suggests the annihilation of lattice phonons, which is a signature of optical cooling. 21 Panels A and B of Figure 2 show normalized X-ray absorption near-edge structure (XANES) spectra of double and quadruple molybdates with different La/Dy ratios, respectively.…”
mentioning
confidence: 98%
“…The data show that these molybdates crystallize in a tetragonal I4 1 /a-type unit cell comprising interconnected MO 4 tetrahedral and REO 8 dodecahedral building blocks. 14 connected by a RE−O−Mo−O−RE motif with a RE−RE distance of 6.48 Å. 14,18,19 In this work, we excite 4d → 4f transitions of lanthanum cations using soft X-rays and examine the optical response of Dy 3+ ions incorporated in the rare-earth sublattice.…”
mentioning
confidence: 99%
See 1 more Smart Citation